2003
DOI: 10.2343/geochemj.37.545
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and boron isotopic compositions of tourmaline from the Lavicky leucogranite, Czech Republic

Abstract: Abundant tourmaline occurs in the Lavicky leucogranite, Czech Republic as spherical to ovoid quartztourmaline orbicules, typically 5 to 7 cm in diameter. The tourmalines also occur as fine-grained quartztourmaline veins (<1 cm thick) that cut the orbicule-rich granite. Electron microprobe analyses reveal that tourmaline from the quartz-tourmaline orbicules is Fe-rich schorl with a range of Fe/(Fe+Mg) ratio 0.62 to 0.77 and Na/(Na+Ca) ratio 0.82 to 0.95. In contrast, tourmaline from quartz-tourmaline veins is M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
4
22
4
Order By: Relevance
“…Many empirical studies of B-isotopes in tourmaline from igneous and metamorphic rocks and from hydrothermal veins found significant variations in δ 11 B between early and late tourmaline generations, sometimes in single zoned crystals, which were interpreted in terms of temperaturedependent isotopic fractionation during crystal growth (Smith and Yardley, 1996;Chaussidon and Appel, 1997;Jiang and Palmer, 1998;Nakano and Nakamura, 2001;Matthews et al, 2003;Jiang et al, 2003; this paper). However, there are also examples of isotopic homogeneity in zoned or polyphase tourmaline growths that argue against significant fractionation effects (Tonarini et al, 1998;Marschall et al, 2006).…”
Section: Boron Isotope Fractionation Among Tourmaline Fluids and Gramentioning
confidence: 99%
See 1 more Smart Citation
“…Many empirical studies of B-isotopes in tourmaline from igneous and metamorphic rocks and from hydrothermal veins found significant variations in δ 11 B between early and late tourmaline generations, sometimes in single zoned crystals, which were interpreted in terms of temperaturedependent isotopic fractionation during crystal growth (Smith and Yardley, 1996;Chaussidon and Appel, 1997;Jiang and Palmer, 1998;Nakano and Nakamura, 2001;Matthews et al, 2003;Jiang et al, 2003; this paper). However, there are also examples of isotopic homogeneity in zoned or polyphase tourmaline growths that argue against significant fractionation effects (Tonarini et al, 1998;Marschall et al, 2006).…”
Section: Boron Isotope Fractionation Among Tourmaline Fluids and Gramentioning
confidence: 99%
“…Such tourmaline-quartz segregations are known from several other boron-rich granites (e.g., Schust et al, 1970;Sinclair and Richardson, 1992;Taylor et al, 1992;Trumbull, 1993;Rozendaal and Bruwer, 1995;London, 1999;Jiang et al, 2003). Their origin is still not well understood, but it has been suggested that unmixing of a boron-rich late magmatic/early hydrothermal fluid from evolved granitic magma is involved (Samson and Sinclair, 1992;Taylor et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, the analysis of boron isotope compositions in geological samples, in particular those with complex matrices such as tourmaline, is a challenging task (Gonfiantini et al, 2003;Tonarini et al, 2003). In 2003, we reported extremely negative boron isotope compositions of tourmaline from the Lavicky granite (Jiang et al, 2003), and these values have been proven to be wrong as they are not supported by new SIMS analysis on tourmalines from the same granite (Marschall and Ludwig, 2006). We thank Marschall and Ludwig for pointing out the problem, and will take this lesson into account in our future boron isotope studies.…”
Section: Introductionmentioning
confidence: 90%
“…Tourmaline samples from the Lavicky granite were decomposed using the acid digestion method (HF + HNO 3 ), purified through column chemistry, and the 11 B/ 10 B ratio determined using the N-TIMS method (Jiang et al, 2003). After publication of these extreme negative δ 11 B values for the Lavicky tourmalines, we noted that an abstract published in Geochemica et Cosmochimica Acta (2003, Suppl., A577) also reported very negative δ 11 B values from -41.1 to -9.2 per mil in tourmalines from the Altay No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation